Economic impact of periprosthetic hip fractures - D. González-Martín; J.L. Pais-Brito; S. González-Casamayor; A. Guerra-Ferraz; J.M. González-Pérez; A. Jiménez-Sosa; M. Herrera-Pérez (Revista Española de Cirugía Ortopédica y Traumatología, 2022)
Introduction: Hip replacement is one of the most successful operations in orthopaedic surgery. Periprosthetic hip fractures (PPHF) have very serious consequences for the patient, and they also entail a very important economic impact on healthcare systems. The aim of the study was to provide the first detailed cost analysis of PPHF in a traumatology and orthopaedics service in a third level hospital in Spain. Methods: The study included all patients admitted between 2009 and 2019 with a diagnosis of “PPHF”. We assessed hospital stay cost, total cost of the operating theatre, cost of the implants used, analyses, consultations with other specialists, rehabilitation sessions, radiological tests, microbiology, blood transfusions and other surgical operations during the same admission. Results: 78 patients were included in the study, 49 women and 29 men, with a mean age of 78.74 years (R 45–92). 69 patients received surgical treatment, 75% had open reduction and internal fixation (ORIF), and 25% had revision surgery. The total cost was €1,139,650.17. The average cost was €14,610.90. Significantly higher costs were incurred for revision compared to ORIF treatments, admissions that lasted more than 30 days, and patients who required more than one operation during admission. The most costly factors were the hospital stay (46%), the cost of the surgery itself (35%), and the implants (24%). Conclusions: Revision arthroplasty versus ORIF treatment, admissions lasting more than 30 days, and patients requiring more than one operation on admission incurred significantly higher costs. The average cost, from a hospital perspective, generated by a PPHF was €14,610.90. The most costly factors were, in descending order, the hospital stay, the cost of the surgery itself, and the implants. It is necessary to establish protocols and updated therapeutic algorithms in the perioperative management of PPHF in order to reduce both morbidity rates and associated costs. Resumen: Introducción: La artroplastia de cadera es una de las operaciones con mejores resultados en cirugía ortopédica. Las fracturas periprotésicas de cadera (FPPC) tienen consecuencias muy graves para el paciente y además suponen un impacto económico muy importante para los sistemas sanitarios. El objetivo del estudio es realizar el primer análisis detallado de los costes de las FPPC en un Servicio de Cirugía Ortopédica y Traumatología en un hospital universitario de tercer nivel en España. Métodos: El estudio incluyó a todos los pacientes ingresados entre 2009 y 2019 con el diagnóstico de «FPPC». Se evaluaron el coste de la estancia hospitalaria, el coste total del quirófano, el coste de los implantes utilizados, los análisis de sangre, las consultas con otros especialistas, las sesiones de rehabilitación, las pruebas radiológicas, la microbiología, las transfusiones de sangre y otras intervenciones quirúrgicas durante el mismo ingreso. Resultados: Se incluyó a un total de 78 pacientes, 49 mujeres y 29 hombres, con una edad media de 78,74 años (R 45-92); 69 pacientes recibieron tratamiento quirúrgico, el 75% se sometió a reducción abierta y fijación interna (RAFI) y el 25% a revisión protésica. El coste total fue de 1.139.650,17 €. El coste medio fue de 14.610,90 €. Los costes fueron significativamente más elevados en la revisión protésica que en la RAFI, en los ingresos que duraron más de 30 días y en los pacientes que requirieron más de una intervención quirúrgica durante el ingreso. Los factores que más influyeron en el coste fueron la estancia hospitalaria (46%), el coste de la intervención quirúrgica (35%) y el de los implantes (24%). Conclusiones: La cirugía de revisión protésica frente a RAFI, los ingresos de más de 30 días y los pacientes que requirieron más de una intervención quirúrgica durante el ingreso supusieron costes significativamente mayores. El coste medio, desde el punto de vista hospitalario, generado por una FPPC fue de 14.610,90 €. Los factores que más influyeron en el coste, en orden decreciente, fueron la estancia hospitalaria, el coste de la intervención quirúrgica y el de los implantes. Es necesario establecer protocolos y algoritmos terapéuticos actualizados en el manejo perioperatorio de la FPPC para reducir tanto las tasas de morbilidad como los costes asociados.